LGR5‐Positive Colon Cancer Stem Cells Interconvert with Drug‐Resistant LGR5‐Negative cells and are Capable of Tumor Reconstitution123. (27th November 2012) - Kobayashi, Shinta; Yamada‐Okabe, Hisafumi; Suzuki, Masami; Natori, Osamu; Kato, Atsuhiko; Matsubara, Koichi; Jau Chen, Yu; Yamazaki, Masaki; Funahashi, Shinichi; Yoshida, Kenji; Hashimoto, Eri; Watanabe, Yoshinori; et al.
Abstract: The cancer stem cell (CSC) concept has been proposed as an attractive theory to explain cancer development, and CSCs themselves have been considered as targets for the development of diagnostics and therapeutics. However, many unanswered questions concerning the existence of slow cycling/quiescent, drug‐resistant CSCs remain. Here we report the establishment of colon cancer CSC lines, interconversion of the CSCs between a proliferating and a drug‐resistant state, and reconstitution of tumor hierarchy from the CSCs. Stable cell lines having CSC properties were established from human colon cancer after serial passages in NOD/Shi‐ scid, IL‐2Rγ null (NOG) mice and subsequent adherent cell culture of these tumors. By generating specific antibodies against LGR5, we demonstrated that these cells expressed LGR5 and underwent self‐renewal using symmetrical divisions. Upon exposure to irinotecan, the LGR5 + cells transitioned into an LGR5 − drug‐resistant state. The LGR5 − cells converted to an LGR5 + state in the absence of the drug. DNA microarray analysis and immunohistochemistry demonstrated that HLA‐DMA was specifically expressed in drug‐resistant LGR5 − cells, and epiregulin was expressed in both LGR5 + and drug‐resistant LGR5 − cells. Both cells sustained tumor initiating activity in NOG mice, giving rise to a tumor tissue hierarchy. In addition, anti‐epiregulin antibody was found to be efficacious in a metastatic model. Both LGR5 + and LGR5 − cells were detected in the tumor tissues of colon cancer patients. The results provide new biological insights into drug resistance of CSCs and new therapeutic options for cancer treatment. STEM CELLS 2012;30:2631–2644